AESTHETIC FORM OF LEMBU SURO DANCE PERFORMANCE IN KELURAHAN JAGALAN KECAMATAN JEBRES SURAKARTA CITY - Lestari, Sukmajati Kartika Budi; Indriyanto, Indriyanto (Sembadra, Journal of Arts and Education Studies, 2021)
Lembu Suro dance is a dance originating from Jagalan Subdistrict, Jebres District, Surakarta City which depicts a symbol of the people who dare to defend the truth and dare to sacrifice for the people. Lembu Suro dance has a distinctive impression of beauty that characterizes the dance. The beauty is in the form of the show through its elements. The purpose of this research is to find out, find, describe the aesthetics of Lembu Suro Dance Performance in Jagalan Village, Jebres District, Surakarta City. This research uses a research approach of a descriptive qualitative approach, a choreographic structure approach and an emic ethical approach. Data collection techniques used were observation, interviews, and documentation. The data validity technique used triangulation. Triangulation of sources, triangulation of techniques and triangulation of time. The data obtained were then analyzed by describing the components in the dance performance, understanding between the components, and interpreting the value of beauty. The results of this study can be obtained an overview related to the Aesthetics of Lembu Suro Dance Performance which includes the Aesthetics of Performance Forms, Performance Patterns, Performance Elements, and Appraisal of the beauty resulting from subjective and objective beauty assessments. Keywords: Aesthetic, Form of the Art Performance, Lembu Suro Dance